Neuroprotective effect of Baillonella toxisperma Pierre on the oxidative stress status in an experimental animal model of Alzheimers disease - Ghislain, Djiokeng Paka; Dany Joel, Ngoumen Ngassa; Janvier, Youovop Fotso; Mary-Ann, Mbong Angie; Laure, Ngondi Judith; Oben, Julius Enyong (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Recent research findings have shown that neurodegenerative disorders like Alzheimer are partly caused by increased levels of reactive oxygen species. The present study aims to investigate the effect of Baillonella toxisperma on an oxidative stress status induced by aluminium chloride in female rats. Hydroethanolic extract of B. toxisperma (HEEBT) was selected after evaluation of antioxidant potential using four methods notably TAC (total antioxidant capacity), scavenging of 1, 1-Diphenyl-2-Picrilhydrazyl (DPPH), hydroxyl radical (·OH) and inhibition of lipid peroxidation. It was used to evaluate neuroprotection in female albino wistar rats that were intoxicated with aluminium chloride. Twenty-five rats were divided into five groups of five rats each; group 1: control group, group 2: AlCl3 exclusively treated (32.5 mg/kgBW) and served as positive control; group 3, 4 and 5 were treated with AlCl3 and either 150/300mg/kgBW of HEEBT or 100mg/kgBW vitamin E daily for three days 24H after administration of AlCl3. After treatment, animals’ blood and brain were collected. Hydroperoxide (ROOH), Malondialdehyde (MDA) and protein thiol levels were determined in brain homogenates while ALT, AST, protein and creatinine levels were evaluated in plasma and catalase in erythrocytes. The in vitro antioxidant activity of the HEEBT was better than for ethanolic and aqueous extracts. Results of biochemical analysis of brains of female rats revealed that AlCl3 significantly (p<0,05) increased MDA levels (3,97 vs 7.32 µM) and the activity of catalase (0.020 vs 0.096 mMH2O2/min/mg of proteins) in female rats. In contrast, female rats treated with HEE of B. toxisperma (150 and 300 mg/kg/day b.wt) showed a significant decrease (p<0,05) of MDA levels (4.43 and 4.58 µM) and the activity of catalase (0.045 and 0.054 mMH2O2/min/mg of proteins). The results obtained for toxicity markers (AST, ALT and creatinine) have the same profile. Hydroethanolic extract of B. toxisperma have antioxidant and neuroprotective effects by scavenging free radical and protecting neurons cells against oxidative damage induced by aluminum chloride.